Word Learning: Homophony and the Distribution of Learning Exemplars. Issue 3 (2nd July 2016) - Dautriche, Isabelle; Chemla, Emmanuel; Christophe, Anne
ABSTRACT: How do children infer the meaning of a word? Current accounts of word learning assume that children expect a word to map onto exactly one concept whose members form a coherent category. If this assumption was strictly true, children should infer that a homophone, such as "bat", refers to a single superordinate category that encompasses both animal-bats and baseball-bats. The current study explores the situations that lead children to postulate that a single word form maps onto several distinct meanings, rather than a single superordinate meaning. Three experiments showed that adults and 5-year-old French children use information about the sampling of learning exemplars (and in particular the fact that they can be regrouped in two distinct clusters in conceptual space) to postulate homophony. This unexplored sensitivity and the very possibility of homophony are critically missing from current word learning accounts.